INHIBITING FACTORS IN THE ENFORCEMENT OF CRIMINAL LAW AGAINST ILLEGAL MINING: A CASE STUDY IN SOUTH SUMATRA - M Indra Parameswara; Ruben Achmad; Hambali Yusuf (Jurnal Ilmiah Advokasi, 2025)
Mineral and coal resources in Indonesia, particularly in South Sumatra Province, are non-renewable natural resources whose management is constitutionally mandated to be controlled by the state for the greatest benefit of the people. Despite this mandate, illegal mining activities remain widespread and pose serious challenges to criminal law enforcement. This study aims to analyze the inhibiting factors affecting the effectiveness of criminal law enforcement against illegal mining crimes within the jurisdiction of the South Sumatra Regional Police. This research employs a normative juridical method using statutory and conceptual approaches, supported by an analysis of law enforcement practices. The findings indicate that the primary obstacles to effective law enforcement stem from internal factors within law enforcement institutions, including limited personnel capacity, inadequate competence, corrupt practices, conflicts of interest, and insufficient facilities and infrastructure. These constraints are exacerbated by the high number of illegal mining cases, with at least 77 cases recorded over the past three years, which overwhelms the existing institutional capacity. The study concludes that strengthening institutional capacity, enhancing professionalism and integrity of law enforcement officers, improving inter-agency coordination, and providing adequate resources are essential to ensure effective, fair, and sustainable criminal law enforcement against illegal mining activities.Keywords: inhibiting factors, criminal law enforcement, illegal mining